Efecto sinérgico in vitro del aceite esencial de Origanum vulgare con Imipenem sobre pseudomonas aeruginosa - Pesantes Calderón, Juan Manuel (2018)
To evaluate in vitro synergic effect of the essential oil of Origanum vulgare (EOOV) with Imipenem on Pseudomonas aeruginosa. Materials and methods: The experimental design was developed in 2 phases: in the first phase, the effect of EOOV and Imipenem on Pseudomonas aeruginosa was evaluated by diffusion disc and macrodilution in broth method, 10 repetitions were performed for each treatment. In the second, the minimum inhibitory concentration (MIC) was obtained for the EOOV and Imipenem, subsequently the synergic effect between EOOV and Imipenem was determined by the "checkerboard" method. Results: The susceptibility of Pseudomonas aeruginosa to EOOV was 6.5mm, 8.2mm, 11.4mm and 16.5mm at 25%, 50%, 75% and 100% respectively and the susceptibility to Imipenem was 37.3mm. The MIC of EOOV and Imipenem was 697.5ug / ml and 4ug / ml respectively. The MIC of the EOOV with Imipenem using the technique "Checkerboard" was 30.51563 ug / ml and 1ug / ml respectively The fractional inhibitory concentration (FIC) between the EOOV and Imipenem ranged between 0.29 and 0.42 Conclusion: The EOOV does have synergistic in vitro effect with Imipenem on Pseudomonas aeruginosa